Pengaruh Tata kelola Kolaborasi dan UU Cipta kerja Terhadap Perkembangan UMKM Disaat Pandemi Covid 19 - Aidi, Ahmadi (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
This research is related to the development of MSMEs in Indonesia. The dependent variable used in this study is the development of MSMEs during the Covid 19 pandemic, while the independent variables are collaborative governance and the Omnibus  Law. The power of sharing in collaborative use of social media is the key to the success of MSME marketing during the COVID-19 pandemic. The Omnibus Law encourages the strengthening of the MSME ecosystem through various facilities, including ease of licensing, certification, financing, market access, training, digital infrastructure, implementation of electronic systems and transactions, as well as the business climate in the MSME sector. The purpose of this study was to determine and analyze the influence of collaborative governance and the Omnibus Law on the development of MSMEs during the Covid 19 Pandemic. The method used in this research is descriptive quantitative by taking a sample of 30 MSME actors in Jakarta. The conclusion of this study is that there is a significant influence between collaborative governance and the Omnibu Law on the development of MSMEs during the Covid-19 Pandemic